Effect of brimonidine on central corneal thickness in normal tension glaucoma patients - V., Neethu K.; V., Latha N.; K., Praveena K. (International Journal of Research in Medical Sciences, 2019)
Background: Brimonidine is a potent ocular hypotensive agent widely used in glaucoma treatment. A reduction in central corneal thickness can lead to an underestimation of intraocular pressure by Goldmann applanation tonometry and vice versa. The aim of this study is to determine whether brimonidine has an effect on central corneal thickness. Methods: 30 eyes of patients who attended the Ophthalmology OPD between the time period October 2017 and June 2018 who were newly diagnosed with normal tension glaucoma with no history of any systemic illness or not on any medication were included. Each patient underwent a complete ophthalmic evaluation including fundus examination, visual field assessment, intraocular pressure, central corneal thickness measurement by pachymetry before as well as 1 month and 6 months after starting treatment with 0.2% topical brimonidine twice daily. Results: Administration of brimonidine 0.2% resulted in an increase in central corneal thickness from 525±21 µm before starting brimonidine to 528±21 µm (p<0.05) after 1 month and 535±20 µm (p<0.001) after 6 months. It also resulted in a reduction in intraocular pressure from an initial value of 16±2 mmHg before starting brimonidine to 14±2 mmHg (p<0.05) and 13±2 mmHg (p<0.05), 1month and 6 months after starting treatment, respectively. Conclusions: The data presented in this study show that topical administration of 0.2% brimonidine twice daily results in a significant increase in central corneal thickness in patients with normal tension glaucoma.